Australian Research Related to Sporting and Musculoskeletal Injuries of the Foot and Ankle: A Bibliometric Analysis - Peterson, Benjamin; Osborne, John; Azhar, Ameer Nor; Carroll, Matthew; Tehan, Peta (Wiley, 2026)
Background There is growing research evidence related to musculoskeletal and sports podiatry published by Australian researchers. This short report presents data from the musculoskeletal and sports podiatry stream of a national bibliometric review which aimed to map all Australian podiatry-related research from 1970 to 2024. Methods A systematic search of the literature was conducted via Scopus until December 2024. Studies were screened for eligibility using Covidence. Study meta-data was analysed using Biblioshiny to describe publications volume, authors, institutions, journals, and research collaborations. Via manual processes, each publication was categorised for: level of evidence using National Health and Medical Research Council criteria; research type using the United Kingdom Clinical Research Collaboration Health Research Classification System; and funding source, using Higher Education Research Data Collection specifications. Results The search strategy yielded 288 records published by 774 authors (19% international), with a total 12,593 citations, with 44.1 mean citations per article from 1991 to 2024 were included. A total of 65 articles (23%) were categorised as level I evidence. The British Journal of Sports Medicine and the Journal of Science and Medicine in Sport were equally the most frequent publication sources, publishing 23 (8%) articles respectively. Podiatry-related musculoskeletal and sports research is usually undertaken without dedicated funding (67%). The majority of published articles focussed on the evaluation of treatments and therapeutic interventions (36%) and on the aetiology of conditions (34%). Conclusion The musculoskeletal and sports podiatry stream was the most widely researched, with the highest proportion of level I evidence among all streams of the national bibliometric review. Given the high burden of disease and adverse impacts on activities of daily living associated with musculoskeletal conditions, further attention in preventative care and the promotion of wellbeing in sports and musculoskeletal research would be beneficial.
Keywords: 1103 Clinical Sciences; 1104 Complementary and Alternative Medicine; 1106 Human Movement and Sports Sciences; 3202 Clinical sciences; 4201 Allied health and rehabilitation science; 4207 Sports science and exercise; ankle; biomechanics; foot; musculoskeletal; publications; research; sports